PENERAPAN METODE SIMPLE ADDICTIVE WEIGHTING (SAW) UNTUK MENENTUKAN KELAYAKAN PENERIMA BEASISWA KARTU INDONESIA PINTAR (KIP) KULIAH - Sasmita Sasmita; Alfis Arif (JITEK (Jurnal Ilmiah Teknosains), 2021)
AbstractThis review means to deliver a choice emotionally supportive network utilizing the Simple Addicitive Weighting (SAW) technique to decide the qualification of KIP College grant beneficiaries. The foundation of this exploration is that in deciding the beneficiaries of the KIP Lecture grants, STT Pagar Alam actually utilizes the ordinary framework, to be specific planned understudies gather documents and step through different exams, then, at that point, understudy information will be contrasted and the measures individually. Choice emotionally supportive network is a PC based data framework to help people in settling on a choice. The improvement strategy utilized is Waterfall which comprises of examination, plan, coding, testing and upkeep/support. The Simple Addictive Weighting (SAW) strategy will be applied in settling on this choice emotionally supportive network. This strategy was picked on the grounds that this technique decides the weight an incentive for each characteristic, then, at that point, continues with positioning which will choose the best option from various other options. This choice emotionally supportive network was made utilizing the PHP programming language with the codeigniter 3 structure. Testing this framework utilizing discovery testing with a score of 3.6 from master survey and 3.8 from the execution of beta restatement with substantial classifications so a framework for carrying out the Simple Addictive Weighting technique can be delivered. SAW) to decide the qualification of the beneficiaries of the KIP College grants.